BIOSURFACTANTS PRODUCTION BY Pseudomonas aeruginosa USING SOYBEAN OIL AS SUBSTRATE - Venty Suryanti; Sri Hastuti; Tutik Dwi Wahyuningsih; Mudasir Mudasir; Dina Ika Muliawati (Universitas Gadjah Mada, 2009)
Optimization condition of the biosurfactants production by P. aeruginosa using soybean oil as substrate has been examined. The media containing 10% v/v of the soybean oil and 6 days of the fermentation time was the optimum condition for the biosurfactants production. The extraction technique using different solvent polarity (n-hexane, chloroform, ethyl acetate and buthanol, respectively) was applied for the isolation of the biosurfactants. The biosurfactant was found in the extract chloroform of the crude biospasoy (biosurfactants obtained from soybean oil as substrate) which then is called chlo-biospasoy. The chlo-biospasoy was identified as rhamnolipids which had oil in water (o/w) emulsion type, had the CMC of 860 mg/L and could reduced the surface tension of the water from 72 mN/m to 52 mN/m. The chlo-biospasoy could be used as an emulsifier to form emulsion between water and hydrocarbon such as palm oil, benzene, premium or toluene with various stability. The results indicated that chlo-biospasoy could be used as an emulsifying and emulsion-stabilizing agent.